Analisa Efektivitas Pemasangan Multirod-Grounding pada SUTET 500kV Mandirancan-Pemalang Line 3&4 dengan Metode Paired Sample T-Test - Ghani, Reza Muhammad; Putri Hapsari, Jenny (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2025)
Abstract — PLN's customer growth continues to increase every year, with an average increase of 5.26% from 2014 to 2023. Reliability is needed in the 500kV Mandirancan-Pemalang line 3 & 4 SUTET transmission system which distributes electricity from the Batang PLTU and Tanjungjati PLTU. Throughout 2022 and 2023, there were 5 reclose disturbances caused by lightning on the SUTET in the ULTG Tegal. Efforts to prevent lightning disturbances are to reduce the tower grounding resistance value. The method used is to add several grounding rods (Multirod Grounding/MRG) to each tower leg that is struck by lightning and other towers next to it, in front (5 towers) and behind (5 towers). So that it is hoped that the lightning current can be quickly channeled to the ground. The data analysis method used is the paired sample t-test by processing data from grounding resistance measurements on 53 SUTET towers before and after the installation of MRG. Data processing is done using the Data Analysis feature in Microsoft Excel. Based on field measurements, the average grounding resistance value before and after the installation of MRG is 3.75 Ω and 1.33 Ω. Based on data analysis using the Paired Sample T Test method, obtained tcount (tstat)>ttable (tcritical one-tail) with a value of 7.29>2.34 and the P-value (P(T<=t) one-tail)<α(alpha) with a value of 2.97888×10−12<0.01. From these results, the null hypothesis is rejected and the alternative hypothesis is accepted that there is a very significant difference between the grounding resistance of the tower before and after the installation of MRG, so that the installation of MRG is statistically effective. Based on the 2024 disturbance data, there was no disturbance caused by lightning on this SUTET transmission, so that the installation of MRG had an effect on reducing the frequency of lightning disturbances on this SUTET. Keywords — grounding resistance, multirod grounding (MRG), paired sample t-test